Material Characterization of Byzantine Period Brick Masonry Walls Revealed in Istanbul (Turkey) - Ulukaya, Serhan; Yoruc, Afife Binnaz Hazar; Yuzer, Nabi; Oktay, Didem (BUDAPEST UNIV TECHNOLOGY ECONOMICS, 2017)
In this study, the characteristics of mortars and bricks used in the walls of the historical building, which were revealed during the subway station construction excavations, probably belonged to religious place, have been investigated. Results of the analyses indicated that the mortars are hydraulic but they have a low compressive strength and a high porosity. The bricks whatever used as masonry unit or aggregate were produced from calcium rich clay at a firing temperature of 850-900 degrees C, they are of low apparent density, high porosity and relatively high compressive strength, and also show pozzolanic activity.
Keywords: characterization; byzantine mortar; byzantine brick; advanced analysis methods; mechanical properties; BEHAVIOR; MORTARS; Engineering